Offshore refuges support higher densities and show slower population declines of wintering Ruddy Turnstones Arenaria interpres. Issue 4 (2nd October 2019) - Whittingham, Mark J.; McKenzie, Ailsa J.; Francksen, Richard M.; Feige, David; Cadwallender, Tom; Grainger, Matthew; Fazaa, Nadheer; Rhymer, Caroline; Wilkinson, Catherine; Lloyd, Pauline; Smurthwaite, Ben; Percival, Steve M.; et al.
ABSTRACT: Capsule: Wintering Ruddy Turnstones Arenaria interpres occur in higher densities and their populations decline less on, or close to, offshore refuges than on mainland sites subject to greater levels of human disturbance. Aim: To compare wintering densities of Ruddy Turnstones and changes in counts across time from sites with differing levels of human disturbance. Methods: Long-term counts of Ruddy Turnstones (1998/1999 to 2015/2016) were used from 19 sites (two offshore refuges and 17 mainland sites subject to higher levels of human disturbance) in northeast England. No direct measure of human disturbance was available for our mainland sites; instead we used questionnaires ( n = 690) to understand how far people travelled to visit the coast and then used this distance with human population densities in a buffer around each site as a proxy for human disturbance levels. Results: After controlling for the extent of their preferred habitat at each site (rocky shore) we found: (i) the closer each of the 19 sites was to the nearest offshore refuge the higher the density of Ruddy Turnstones and (ii) bird counts were stable at the two refuge sites, whereas, on average, counts declined at the 17 mainland sites. However, no relationship was found between Ruddy Turnstone counts from 17 mainland sites and human population densities within differing distances from each site (up to 10 km). Conclusions: Our work suggests that Ruddy Turnstones made greater use of relatively undisturbed areas (offshore refuges) than those subject to greater disturbance by humans (mainland sites). Although the use of refuges and mainland in our study area was not well known, observations from 11 radio-tagged Ruddy Turnstones suggest that individual birds did use both locations. In a broader context, our work concurs with other studies that highlight the need for refuges with limited or no human access.